Motivation and Public Service Performance: The Role of Organizational Identification - Sri Mutiah Husaini; Haliah; Andi Kusumawati (Indonesian Journal of Business Analytics, 2024)
The aim of writing this article is to present a literature review on motivation, public service performance and the role of organizational identification. Motivation is the main factor in increasing the effectiveness provided by employees in the public sector. The importance of public services is the key to increasing public satisfaction with public sector performance and good performance can also build a positive image of an agency. This is why it is important to build good relations between government and society.The method used in this research is the Systematic Literature Review (SLR) Method. The SLR method is used to collect, identify, analyze and summarize everything available with relevant topic areas with data obtained from articles, books or various other related sources in 2019-2024.